Enabling multimodal interaction in web-based personal digital photo browsing - Ismail, N. A; O'Brien, E. A (2008)
Retrieval process of both digital photos and physical photos has not been easy, especially when the collections grow into thousands. In this paper, we describe an interactive web-based photo retrieval system that enables personal digital photo users to accomplish photo browsing by using multimodal interaction. This system not only enables users to use mouse clicks input modalities but also speech input modality to browse their personal digital photos in the World Wide Web (WWW) environment. The prototype system and it architecture utilize web technology which was build using web programming scripting (JavaScript, XHTML, ASP, XML based markup language) and image database in order to achieve its objective. All prototype programs and data files including the user’s photo repository, profiles, dialogues, grammars, prompt, and retrieval engine are stored and located in the web server. Our approach also consists of human-computer speech dialogue based on photo browsing of image content by four main categories (Who? What? When? and Where?). Our user study with 20 digital photo users showed that the participants reacted positively to their experience with the system interactions.